Study of Pb adsorption by carbon nanofibers (CNFs) grown on powdered activated carbon - Ahmed, Yehya M.; Al-Mamun, Abdullah; Muyibi, Suleyman Aremu; Al-Khatib, Ma'an Fahmi Rashid; Jameel, Ahmed Tariq; Al-Saadi, Mohammed A. (Asian Network for Scientific Information, 2010)
The sorption of lead (Pb) from aqueous solutions by using carbon nanofibers (CNFs) grown on nickel impregnated Powdered Activated Carbon (PAC) was studied. In this study, we investigated the affection of the lead initial concentration on the sorption of the heavy metal from water. The isotherm of the sorption of the heavy metal onto the nanocomposite was also studied. Firstly, the optimum pH for the sorption of the lead ions was determined. The maximum sorption capacity of the heavy metal onto the adsorbent was achieved at initial pH of 5.5. The effects of initial lead ions concentration were examined and the results showed that the adsorption capacities of the carbon nanofibers to uptake the heavy metal increased from about 16 to 89 mg g-1 with increasing the initial lead concentration from 5 to 70 mg L-1. The process sorption could be best fitted by the Langmuir isotherm. The equilibrium sorption capacities of lead ion were determined and found to be 100 mg g-1.